GAMBARAN KARAKTERISTIK IBU POST SECTIO CESAREA TERKAIT PENYEMBUHAN LUKA - Ekawati Saputri, Saputri; Iis Afrianty; Evodius Nasus (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Sectio caesarea is a delivery method that is carried out by making an open incision in the uterine wall, causing wounds in the abdominal area. Globally, around 21% of caesarean section deliveries occur. In Indonesia, caesarean section delivery is around 17.6%. This study aims to determine the characteristics of post-cesarean section mothers regarding wound healing. This research is descriptive quantitative research with a Secondary Data Analysis (ADS) approach. The total sample was 136 using purposive sampling technique. The results of this study show that the characteristics of mothers post cesarean section are that most of them are aged 20-35 years (76.5%) with secondary education level (46.3%), multiparous (69.1%), and have no history of CS (56, 6%) and did not suffer from anemia (61.8%). Almost all of the wounds experienced by mothers after caesarean section were dry wounds (99.3%). The post caesarean section wound is healing well.